A critical evaluation of the dispute resolution functions of the Commission for Conciliation, Mediation and Arbitration (CCMA) - Kwakwala, Blazius Oscar Kasungula (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MComm (Industrial Psychology))--University of Stellenbosch, 2010.